Comparative evaluation of American Cancer Society and American Lung Association smoking cessation clinics. - Lando, H A (1990)
We compared the effectiveness of American Cancer Society, FreshStart, American Lung Association, Freedom from Smoking, and laboratory clinic methods in subjects (N = 1041) from three communities. Three-month follow-up results favored the laboratory method over the two public service approaches on both a prevalence and a sustained abstinence measure. At one-year follow-up, treatment effects for smoking prevalence were no longer significant. However, sustained abstinence results at one-year remained highly significant and favored the more intensive laboratory and Freedom from Smoking clinics over the FreshStart method. FreshStart fared less well than the other interventions both in producing initial quit attempts and in sustaining abstinence among initial quitters. It should be noted, however, that FreshStart requires considerably less facilitator contact than do the other approaches. Unexpected outcome effects occurred for treatment location. Future clinic programs should include a specific target date for quitting and should place more emphasis upon recycling participants who fail to sustain abstinence.